Relevansi Nilai Informasi Laba dan Arus Kas terhadap Harga Saham - Yendrawati, Reni; Pratiwi, Ratna Sari Indah (JDM (Jurnal Dinamika Manajemen), 2014)
The objective of the study was to test the relevance of profit value and cash flow toward the share price in different life cycle stages. The corporate life cycle consists of four stages: start up, growth, mature, and decline stage. This study used secondary data on the companies listed on the Indonesian Stock Exchange in the period of 2010-2012. The samples of this study were 77 companies from manufacture industries. It was a purposive sampling. The data were analyzed by multiple regression analysis using SPSS 17. The results showed that in the mature stage, the analysis accepted the hypothesis that net income are more value relevance than cash flow toward the share price. However, in the growth stage and decline stage, the analysis rejected the hypothesis. This research did not analyze the start-up stage because of the sample data limitation.